Customer Satisfaction Related To Taste, Price, Service And Cafe Design - Erni Rusyani (Institute of Computer Science (IOCS), 2022)
The culinary world from year to year is increasing and competing. Therefore the importance of restaurants to provide maximum service to customers. Therefore, restaurants must create new innovations, have a special taste, and low prices so that consumers feel interested and satisfied when visiting the cafe. This study aims to analyze and determine the effect of taste, price, service and cafe design on consumer satisfaction. The research was conducted at an Upnormal café in the city of Bandung with descriptive research methods with a quantitative approach, the data obtained were by survey methods and sampling techniques using random sampling, data analysis techniques (Structural Equation Modeling - SEM). Then the service received has a significant effect on customer satisfaction. The taste and design of the cafe are accepted but not significant on customer satisfaction. The price is rejected but has a significant effect on consumer satisfaction